Fractures in professional footballers: 7-years data from 106 team seasons in the Middle East - Ngai, Aston; Beasley, Ian; Materne, Olivier; Farooq, Abdulaziz; Tabben, Montassar; Chebbi, Souhail; Ellouze, Zied; Arnáiz, Javier; Alkhelaifi, Khalid; Bahr, Roald; Chamari, Karim (Biology of Sport, 2023)
Epidemiological studies on fractures in European professional football (soccer) are in abundance. However, such data are lacking in Middle Eastern professional footballers and information on fracture treatment is scarce. The aim of this study is to describe the epidemiology of fractures across seven seasons in Qatar Stars League (QSL) footballers. A prospective study of fractures in professional male footballers over 7 consecutive seasons (2013 to 2020), involving 3255 players and 106 team’ seasons. Time loss and injuries and illnesses were recorded using standardised digital tools in accordance with international consensus procedures. Fractures were recorded according to onset mechanism, location, diagnoses, treatment and return to play. A total of 108 players sustained fractures during 638,247 hours of player exposure (88.9% training and 11.1% matches), representing 2.7% of all time-loss injuries. The incidence was 0.17 fractures per 1000 h of exposure (match and training incidence of 0.9 and 0.07 fractures / 1000 h, respectively), equivalent to an average of one fracture per team per season. Fractures mostly occurred in the feet (28.2%), hands (21.1%), shoulders (11.3%) and head (i.e., face) (9.9%). Mean (median) absence was 71 (47 days), with 4.6% refractures. Only 34.3% of the fractures required surgery and nearly all players (98.1%) returned to play at the professional level. Almost all professional football players with fractures return to play at the same competitive level after an average of 10 weeks of absence (mean absence was 71±81 (median: 47, Inter Quartile Range [14–93]) days). One in ten continue to play with symptoms and one in twenty may refracture. Long-term effects of fractures are still unknown.